Molecular Regulation of Satellite Cell Maintenance and Differentiation During Adult Myogenesis - Jones, Andrew E. D. (Université d'Ottawa / University of Ottawa, 2013)
The post-natal regenerative capacity of skeletal muscle is attributed to myogenic satellite cells, which function as lineage-committed precursors to replace terminally differentiated muscle. The development and differentiation of the satellite cell lineage is regulated by Pax7 and the myogenic regulatory factors. While the expression of Pax7 is vital to the function of the satellite cell compartment, the paired domain alternative splicing events that regulate its DNA binding potential remain elusive. Interestingly, the generation of Pax7 splice variants differentially regulate Myf5 expression. We performed a global analysis of two Pax7 isoforms, which differ by a glycine-leucine dipeptide, to determine how paired domain splicing events modify the ability of Pax7 to regulate target genes. To this end, we observe that although the homeodomain is important for Pax7 binding, these isoform differences in the paired domain can regulate Pax7 targets during myogenesis. In addition to further examining the role of Pax7 during satellite cell proliferation and maintenance, it remains important to understand their downstream differentiation potential. Since activation of the canonical Wnt signalling pathway results in reduced regenerative efficiency in vivo, we undertook a global analysis of satellite cell derived myoblasts to examine their ability to respond to canonical Wnt signalling. We demonstrate that Wnt/β-Catenin signalling drives myogenic differentiation, via the myogenin-dependent control of follistatin expression, further fine-tuning the myogenic differentiation process. The effects of canonical Wnt signalling on myogenic differentiation complement our observations regarding Pax7 alternative splicing during myoblast proliferation and provide a greater comprehensive understanding of the molecular regulation of satellite cell development and differentiation during adult myogenesis.
Keywords: Myogenesis; Satellite Cell; Pax7; Follistatin; Alternative Splicing; Myogenic Differentiation